The The Role Of Crude Oil Price Moderation In The Effect Of Financial Ratio On Cumulative Abnormal Return In The Idx Energi Index Companies - Halim, Christina Angelica (E-Jurnal Akuntansi; Vol 34 No 10 (2024), 2024)
ABSTRAK This study examines the effect of financial ratios on cumulative abnormal returns and the moderating role of crude oil prices in the relationship between financial ratios and cumulative abnormal returns. The research was conducted using a quantitative approach. The statistical analysis technique used is multiple linear regression and moderated regression analysis with IBM SPSS Statistics Version 22. The study examined 51 IDX Energi-indexed companies in 2018-2021 with 148 final samples. The results of the study prove that the financial ratios studied include the current ratio (CR), return on equity (ROE), and debt to equity ratio (DER) which have a positive and significant effect on the cumulative abnormal return (CAR). This study shows that financial ratio analysis in financial statements is an indicator that can describe a company's financial performance. The better a company's financial performance, it can attract investors to invest in the company. This study also proves that the price of crude oil (COP) can strengthen the effect of the current ratio (CR) and debt-to-equity ratio (DER) on the cumulative abnormal return (CAR). However, the price of crude oil (COP) is not able to influence the return on equity (ROE) to the cumulative abnormal return (CAR). The results of this study indicate that the movement of crude oil prices is relevant information in determining investment decisions. The increase in crude oil prices shows investors' expectations that the company's financial performance will improve.